Atores sociais politizados da comunidade surda brasileira: análise de discursos polarizados de caráter político-ideológico sob o viés da abordagem sociológica e comunicacional do discurso - Nascimento, Leoni Ramos Souza (2024)
This study has the general objective of analyzing the multiple representations of social actors, politicized members, in oppositional discourses that testify to the political-ideological split between members of the deaf community on the right and left, between the years 2021 and the first two months of 2023, implemented in the media space. To this end, a discussion is presented around the context of politicalideological polarization driving the socio-discursive change of social actors, which we call politicized members of the deaf community, the discursive arena, the epithets, discredits, and the visible ideological influence, maximizing the distance of what we imagine as an equalitarian struggle of a linguistic minority in a society mostly made up of non-deaf people. This investigation is aligned with a theoretical deepening of Critical Discourse Analysis (Fairclough, 2003; Wodak, 2004), under the bias of the Sociological and Communicational Approach to Discourse, based on a retextualization of Bajoit (2006), in turn, helps in the identification of issues concerning the Struggles for Recognition, Communication for Social Change and the Types of Power present in oppositionist discourses in order to reflect on asymmetrical relationships such as abuse of power, social exclusion, social manipulation, religious intolerance and other types of prejudice. As for the socio-discursive analysis proposal, we rely on Systemic-Functional Grammar to linguistically legitimize the analyses. This area of Linguistic Studies is based on the functionalist studies of Halliday (1985, 1994), which facilitates understanding the resources of language use, choosing some categories of analysis, including those of the Evaluative system. The research is situated in a qualitative-interpretivist paradigm, inserted in the methodological procedure of Textually Oriented Discursive Analysis (Magalhães; Martins; Resende, 2017), research in CDA has a transdisciplinary character and allows epistemic dialogues with critical social theories, for the construction of a fruitful field of study, which encompasses research like this, which involves Deaf Studies and Decolonial Studies. This research seeks to reveal the mechanisms of symbolic construction naturalized through the modes of operation of ideology (Thompson, 2009, 2011) and how the concept of social actors is categorically represented based on discursive events highlighted on digital platforms. The results demonstrate that, within the time frame of the political-ideological polarization analyzed, due to oppositionist discourses, the thesis points to the contradiction of the pathological, prejudiced view of deafness, emphasizing that oppositionist discourses lead the multiple epistemological representations, which are configured as true discursive, polemicized arenas, clearly highlighting the discursive tensions between politicized members of the same national linguistic minority.